To solve the given system of equations using the elimination method, we first rewrite the equations clearly:
- \( 2x + y = 3.5 \) (Equation 1)
- \( -2 + 2y = 2.5 \) (Equation 2)
We can simplify Equation 2:
\[ -2 + 2y = 2.5 \]
Adding 2 to both sides gives us:
\[ 2y = 4.5 \]
Dividing both sides by 2 gives:
\[ y = 2.25 \quad \text{(Equation 3)} \]
Now we substitute the value of \( y \) from Equation 3 into Equation 1:
\[ 2x + 2.25 = 3.5 \]
Next, we isolate \( 2x \) by subtracting 2.25 from both sides:
\[ 2x = 3.5 - 2.25 \] \[ 2x = 1.25 \]
Now, dividing both sides by 2 gives:
\[ x = \frac{1.25}{2} = 0.625 \quad \text{(Equation 4)} \]
So the solution to the system of equations is:
\[ x = 0.625, \quad y = 2.25 \]
In ordered pair form, the solution is:
\[ (0.625, 2.25) \]